Resistance of advanced cassava breeding clones to infection by major viruses in Uganda - Mukiibi, Daniel Rogers; Kawuki, Robert; Okao-Okuja, Geoffrey; Sseruwagi, Peter; Ndunguru, Joseph; Ateka, Elijah Miinda (Crop Protection, 2019)
Cassava brown streak disease (CBSD) and cassava mosaic disease (CMD) are two viral diseases that cause severe yield losses in cassava of up to 100%, thereby persistently threatening food and income security in sub-Saharan Africa. For effective management of these diseases, there is a critical need to develop and deploy varieties with dual resistance to CBSD and CMD. In this study, we determined the response of advanced breeding lines to field infection by cassava brown streak viruses (CBSVs) and cassava mosaic begomoviruses (CMBs). This aim helped in identifying superior clones for downstream breeding. In total, 220 cassava clones, three in uniform yield trials (UYTs) and 217 in a crossing block trial (CBT), were evaluated for virus and disease resistance. Field data were collected on disease incidence and severity. To detect and quantify CBSVs, 448 and 128 leaf samples from CBSD symptomatic and symptomless plants were analyzed by reverse transcription PCR and real-time quantitative PCR, respectively. In addition, 93 leaf samples from CMD symptomatic plants in the CBT were analyzed by conventional PCR using CMB species-specific primers. In the CBT, 124 (57%) cassava clones did not express CMD symptoms. Of the affected plants, 44 (55%) had single African cassava mosaic virus infection. Single Cassava brown streak virus (CBSV) infections were more prevalent (81.6%) in CBT clones than single Ugandan cassava brown streak virus (UCBSV) infection (3.2%). Of the three advanced clones in the UYT, NAROCASS 1 and NAROCASS 2 had significantly lower (P < 0.05) CBSD severity, incidence, and CBSV load than MH04/0300. In the UYT, only 22% of samples tested had CBSVs, and all showed a negative result for CMBs. The low disease incidence, severity, and viral load associated with NAROCASS 1 and NAROCASS 2 is evidence of their tolerance to both CBSD and CMD. Therefore, these two cassava clones should be utilized in CBSD and CMD management in Uganda, including their utilization as progenitors in further virus resistance breeding.